SAFETY EVALUATION ON THE USE OF HIGH ALERT DRUGS IN RSUD ARIFIN ACHMAD RIAU PROVINCE - Khairunnisa, Najwa; Nugraha, Dimas Pramita; Bebasari, Eka; Bebasari, Afdal (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2024)
High alert drugs are drugs that have a high percentage of causing risk of harm to patients. To avoid errors, high alert drugs must be used properly, including storage and marking. The objective of this study was determine the safe use of high alert drugs at Arifin Achmad Hospital in Riau Province. This was a descriptive study that included 68 pharmacy officers. A questionnaire was used to collect data, which was the univariately analysed on a computer system. The result showed that the accuracy of the use of high alert drugs based on the 5 principles was in the good category. As many as 65 people (95.6%) were good at the right patient, 67 people (98.5%) were good at the right drug, 66 people (97.1%) were good at the right time of administration, 65 people (95.6%) were good at the right dose, and 66 people (97.1%) were good at the right route of administration. As many as 67 (98.5%) rated the storage safety and labelling of high alert drugs as good. The conclusion of this study is that the implementation of the five rights principle of medication, storage safety and labelling of high alert drugs at Arifin Achmad Hospital in Riau Province has reached a good level.